Die Plek en Roeping van die Nederduitse Gereformeerde Kerk in ’n Postmoderne Wêreld: Riglyne vir Kerklike Hernuwing - Lategan, L. O. K. (Tydskrif vir Christelike Wetenskap | Journal for Christian Scholarship, 2005)
This article examines the role and position of the church in a postmodern society. The focus of the article is on the Dutch Reformed Church and the current debate within the Afrikaans churches on their role in a changing society. The article refers to three developments which impacted on the role of the church during the last four decades. These developments are the influence of and reaction to the zeitgeist on the identity of the church; the church’s racial understanding and the declining role of the DRC as “state” church in society. The article provides several guidelines for the church to react to the demands from the changing society. The emphasis is laid on the centrality of the Bible and the understanding of contemporary society. The needs of churchgoers in the postmodern world cannot be ignored but should be informed through Biblical guidelines. These guidelines are contextualized.